Bienzymatic Cascade for the Synthesis of an Optically Active O-benzoyl Cyanohydrin - Laura Leemans; Luuk van Langen; Frank Hollmann; Anett Schallmey (Catalysts, 2019)
A concurrent bienzymatic cascade for the synthesis of optically pure (S)-4-methoxymandelonitrile benzoate ((S)-3) starting from 4-anisaldehyde (1) has been developed. The cascade involves an enantioselective Manihot esculenta hydroxynitrile lyase-catalyzed hydrocyanation of 1, and the subsequent benzoylation of the resulting cyanohydrin (S)-2 catalyzed by Candida antarctica lipase A in organic solvent. To accomplish this new direct synthesis of the protected enantiopure cyanohydrin, both enzymes were immobilized and each biocatalytic step was studied separately in search for a window of compatibility. In addition, potential cross-interactions between the two reactions were identified. Optimization of the cascade resulted in 81% conversion of the aldehyde to the corresponding benzoyl cyanohydrin with 98% enantiomeric excess.